The Symbols of Gender-Stereotype in Hans Christian Andersen's the Little Mermaid - Jepri Ali Saiful; Ari Setyorini (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2015)
It is seen that there is an existence of gender-stereotype that unwittingly occurred in children's literature. The gender-stereotype of how man and woman should be and behave considering on his/her proper activities in a real life might be portrayed throughout the symbolizations in which numerous readers do not understand what they are about, whereas those symbols of gender-stereotype are teaching the children the concept of masculinity and femininity. This study thus scrutinizes the symbols of gender-stereotype in Hans Christian Andersen’s The Little Mermaid. The data analysis is in the form of symbols which have the issues of gender-stereotype taken from the original fairy tale of The Little Mermaid in 1836. The aims of this study are to find out the symbols of gender-stereotype and describe the meaning of each symbol. Utilizing descriptive qualitative method, the results of this study are the symbols which have the gender-stereotype of masculinity are “King” related to non-emotional and intellectuality in authority of a man. “Knife” is found allied to the masculinity trait of a strong man and “Sword” is an analogue of a brave, adventurous and intellectual man. Moreover, the symbols of femininity found are the “Mermaid or Siren” is interwoven to such the embodiment of a flirtatious woman. “Long Hair” is germane to a loyal and submissive woman. The last, “Oyster” is represented as a nurturing woman.